Development of an automatic plant monitoring system - Tengku Azmi, Tengku Muhammad Afif; Bhuiyan, Moinul (2014)
Automated system operates without the need of human interaction. The main purpose of an automated system is to ease the human works. Nowadays, human are doing lots of complicated and harsh work. Thus, the need for a system to help them has gradually increased. This paper discuss about the automated plant monitoring system. An automated plant monitoring system is essential because the system can help human to monitor their big plantation field. The study in this field especially in Malaysia, which one of its main productions is agricultural, can help boost the production in this field. The conceptual of an automated plant monitoring system can be seen throughout this paper. This system is provided with humidity, temperature and moisture sensor to detect the most suitable amount of water to be used to water the plant according to coefficient generated with that 3 variables. The system that is equipped with Arduino GSM Shield. Global System for Mobile Communication (GSM) enables the system to be connected to the mobile phone. The component plays an important role in providing feedback directly to the users. Besides, the whole system is power up using the solar-power system. Not only it is a renewable energy source, but it also can reduce the amount of pollution.